Towards realistic atomistic models of nitrocellulose degradation processes - Gibbon, Catriona (Cranfield University, 2022)
Computational chemical modelling has many uses, including in situations involving chemicals that are unstable and mechanisms and reactions are hard to detect. A specific case is the degradation of nitrocellulose, a high energy material. It is known that nitrocellulose breaks down via both hydrolysis and thermolysis, but experimentally it is hard to investigate further, due to expense. Computational chemistry can be used to find the energies related to these reactions, and the effect of surrounding solvents, this information can be used to find optimum conditions for stability and long-term storage. Molecular dynamics can be used to create models of large scale of nitrocellulose, which can then be used as bulk structure for the study of these reactions. A stepping stone for building nitrocellulose systems is to build cellulose systems, a naturally occurring chemical that has been well studied. Cellulose naturally occurs in many different forms, from highly crystalline structures, such as cellulose I𝛼 and I𝛽, to amorphous structures, both of which are important for a full understanding of cellulose. Using cellulose I𝛽 as a starting point, structures of cellulose have been created, and the crystallinity broken by running simulations at high temperatures to form a paracrystalline structure. Periodic boundary conditions have been used to approximate an infinite system. Once accurate structures of cellulose have been created these are nitrated to varying levels of nitration. There are six possible locations of nitration in a cellulose dimer, and the nitrocellulose structures will be created with random combinations of 4-5 nitrated groups per dimer, giving approximately 12 % nitrogen content by mass, a level of nitration that is representative of experimental nitrocellulose.
Keywords: Nitrocellulose'; 'Molecular dynamics'; 'Paracrystalline'; 'DSDS21'; 'DSDS Poster'; 'Computational Chemistry'